Kata alu-aluan NC UTM - Dean, Dean (Faculty of Chemical & Natural Resources Engineering, UTM, 2008)
This is the speech of UTM's Vice-Chancellor in the ‘Menganjak ke Persada Dunia’ which was published to commemorate the FKKKSA’s 25th Anniversary. It was launched by the Vice-Chancellor of Universiti Teknologi Malaysia, Tan Sri Professor. Dr. Mohd. Zulkifli bin Tan Sri Mohd. Ghazali, at the Grand Celebratory Dinner held at the Best Western Premier Seri Pacific Hotel, Kuala Lumpur, on 12 April 2008. ‘Menganjak ke Persada Dunia’ which was written in Malay, also comprises mission and vision of UTM and FKKKSA, information on Department of Petroleum, Chemical, Polymer, Bioprocess, and Gas Engineering, etc.